Assessing the Contributions of Non-Governmental Organizations in Improving Farmers’ Livelihoods in Katsina State, Nigeria - Yusufu, Ahmed Audu; Nzeako, Samuel Uchenna; Obadahun, Oluwatoyin Simon (Kashere Journal of Politics and International Relations, 2024)
This study evaluates the contributions of non-governmental organizations to improving farmers’ livelihoods in Ingawa Local Government Area of Katsina State, Nigeria, with a focus on the efforts of Techno-Serve. Methodologically, the research utilized primary data collected through Key Informant Interviews and secondary data sourced from books, journals, and web-based materials. The primary data obtained from the field survey were qualitatively analysed in alignment with the study's declared objectives. The study employs Performance Failure Theory as its theoretical framework. Findings indicate that respondents reported significant benefits, such as training in best agricultural practices, which enhanced production, reduced post-harvest losses, and increased income. Additional benefits included business skills training, which enabled tomato farmers to form organizations, establish direct market connections with premium buyers, and receive farm input support. However, the study also identified challenges faced by non-governmental organizations, primarily insecurity due to armed banditry. Based on these findings, the study recommends that the state government prioritize the security of lives and property by deploying more security agents equipped with sophisticated weapons to the area. Furthermore, the study suggests that non-governmental organizations should identify and support more farmers to ensure sustainable food production in the state and the country at large.